Pemberian Pendidikan Kesehatan untuk Meningkatkan Pengetahuan Keluarga dalam Merawat Lansia Demensia di Puskesmas Pauh, Kota Padang - Rika Sarfika; Feri Fernandes; Gentri Mailia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
Dementia in the elderly is very worrying today. Because the numbers tend to increase every year. Elderly who have been affected by dementia requires close attention and control to prevent things that can endanger the elderly. Many families feel stressed in caring for the elderly, both physical and psychological stress. There are even families who lock up the elderly in the house for the reasons of elderly safety. This situation can worsen the condition of the elderly who experience dementia. Therefore, it is necessary to carry out activities that can increase the community's knowledge and understanding of dementia and how to treat it. This activity was carried out in RW 3 of Cupak Tangah Pauh, attended by 14 elderly families. Provision of health education using a lectures and demonstrations approach. To find out the level of knowledge of the elderly families before and after the provision of health education used a measuring tool consisting of 5 questions. The results of the activity found that an increase in knowledge after being given health education is the average score of pra-test 3.00 increased to an average of 4.14 at the time of the post-test. Based on the results, it is recommended to nurses at the health center to be able to continue health education to the elderly families as a promotive and preventive program.